Induced Tomato Plant Resistance Against Tetranychus urticae Triggered by the Phytophagy of Nesidiocoris tenuis - Pérez-Hedo, Meritxell; Arias-Sanguino, Ángela M.; Urbaneja, Alberto (Frontiers in Plant Science, 2018)
TThe zoophytophagous predator Nesidiocoris tenuis (Reuter) (Hemiptera: Miridae) is capable of inducing plant defenses in tomato due to its phytophagous behavior. These induced defenses, which include the release of herbivore-induced plant volatiles (HIPVs), have been proven to affect the oviposition behavior and reduce the subsequent performance of some tomato pests. However, the effect of induction of plant defenses by N. tenuis on the preference, development and reproduction of the two-spotted spider mite Tetranychus urticae Koch (Acari: Tetranychidae) remains unknown. In this research, T. urticae did not show preference for the odor source emitted by intact tomato plants when compared with N. tenuis-punctured plants and jasmonic acid deficient mutant tomato plants. Furthermore, the number of eggs laid by T. urticae on intact tomato plants or on N. tenuis-punctured plants was similar. However, in a greenhouse experiment conducted to evaluate whether the defense induction mediated by N. tenuis had an effect on T. urticae the infestation of T. urticae was significantly reduced by 35% on those plants previously activated by N. tenuis when compared to the control. The expression of a JA-responsive gene that was upregulated and the transcription of the plant protein inhibitor II was higher on activated plants relative to the control. These results can serve as a basis for the development of new management strategies for T. urticae based on plant defense mechanisms induced from the phytophagous behavior of N. tenuis.